2002
DOI: 10.1113/jphysiol.2002.018671
|View full text |Cite
|
Sign up to set email alerts
|

Salmon calcitonin – a potent inhibitor of food intake in states of impaired leptin signalling in laboratory rodents

Abstract: To compare the anorectic effectiveness of leptin and the amylin analogue salmon calcitonin (sCT), rodents were treated on 1 day with subcutaneous injections. In chow-fed C57Bl/6J mice, leptin and sCT reduced energy intake and acted additively. After C57Bl/6J mice had become leptin-resistant on being fed chocolate as a palatable high-caloric supplement to chow, their sCT-induced decrease in energy intake was more pronounced than in chow-fed mice with differential changes in the intake of chocolate (strong reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 36 publications
3
36
2
1
Order By: Relevance
“…Our results are contradicting to previous studies showing that sCT decreases lever pressing for palatable reward (Morley et al 1997) and palatable food intake in mice (Eiden et al 2002). However, either these studies used high doses of amylin in the range of 100 to 200 μg/kg in an operant paradigm (Morley et al 1997), or they were conducted in mice resistant to leptin after being scheduled on chocolate as a highly caloric substitute to chow for more than 40 days (Eiden et al 2002). Another difference is that our experiments were conducted in novel cages; thus, novelty could be considered as a factor potentially influencing our data.…”
Section: Discussioncontrasting
confidence: 56%
“…Our results are contradicting to previous studies showing that sCT decreases lever pressing for palatable reward (Morley et al 1997) and palatable food intake in mice (Eiden et al 2002). However, either these studies used high doses of amylin in the range of 100 to 200 μg/kg in an operant paradigm (Morley et al 1997), or they were conducted in mice resistant to leptin after being scheduled on chocolate as a highly caloric substitute to chow for more than 40 days (Eiden et al 2002). Another difference is that our experiments were conducted in novel cages; thus, novelty could be considered as a factor potentially influencing our data.…”
Section: Discussioncontrasting
confidence: 56%
“…This was corroborated by the finding that rats treated with antibodies against IL-6 or mice deficient for IL-6 did not show the same enhancing effect of amylin on leptin signaling compared with their respective controls. 98 Finally, and consistent with earlier studies that leptin-deficient ob/ob mice are less sensitive to sCT, 75 we recently showed that leptin-receptor-deficient db/db mice or Zucker ZDF rats respond less to acute amylin injections than respective wild-type controls; further, the reduction of body weight and adiposity by leptin was lower in amylin-deficient mice than in wild-type controls, 85 and amylin-deficient mice had less leptin-induced pSTAT3 formation in the ventromedial hypothalamus. 85 In other words, endogenous leptin action may be required for a full action of amylin and the presence of amylin signaling may mutually be necessary for the full effect of leptin.…”
Section: Interactions Of Amylin With Other Factors Involved In the Cosupporting
confidence: 76%
“…One of the first studies in respect to amylin reported that rodent models with a defective leptin signaling system have a reduced response to anorectic doses of the amylin agonist sCT. 75 Subsequently, we reported that acute administration of leptin to the third ventricle increased the eating-inhibitory effect of peripheral amylin. 76 Interest in this type of interaction was fueled by the finding that amylin may be able to reduce the leptin resistance that is commonly associated with obesity.…”
Section: Interactions Of Amylin With Other Factors Involved In the Comentioning
confidence: 99%
“…ob/ob and MC4Rko mice, fa/fa rats) require higher doses of the amylin receptor agonist, salmon calcitonin (sCT) to reduce eating [17], suggesting that obesity may attenuate amylin sensitivity. Previous pilot work has also indicated that high circulating amylin levels may reduce the ability of amylin to slow gastric emptying [18].…”
Section: Introductionmentioning
confidence: 99%